2016
DOI: 10.1038/mt.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Functional Restoration of gp91phox-Oxidase Activity by BAC Transgenesis and Gene Targeting in X-linked Chronic Granulomatous Disease iPSCs

Abstract: Chronic granulomatous disease (CGD) is an inherited immunodeficiency, caused by the inability of neutrophils to produce functional NADPH oxidase required for fighting microbial infections. The X-linked form of CGD (X-CGD), which is due to mutations in the CYBB (gp91phox) gene, a component of NADPH oxidase, accounts for about two-thirds of CGD cases. We derived induced pluripotent stem cells (iPSCs) from X-CGD patient keratinocytes using a Flp recombinase excisable lentiviral reprogramming vector. For restoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…A previous study by Laugsch et al 17 demonstrated restoration of gp91 phox expression and ROS activity in iPSCs from a patient with a mutation in exon 7 of CYBB, by utilizing a large bacterial artificial chromosome containing the endogenous sequence of exons 6 through 13 together with the intervening introns, for homologous recombination-mediated replacement of the CYBB mutation without nuclease enhancement. In the current study, TALEN-mediated targeted insertion of a minigene consisting of the normal or codon-optimized cDNA of all 13 exons of CYBB without introns into the start site of exon 1 of the endogenous CYBB gene resulted in no detectable gp91 phox expression, indicating that intronic or other downstream non-coding elements are necessary for expression from the CYBB promoter.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Laugsch et al 17 demonstrated restoration of gp91 phox expression and ROS activity in iPSCs from a patient with a mutation in exon 7 of CYBB, by utilizing a large bacterial artificial chromosome containing the endogenous sequence of exons 6 through 13 together with the intervening introns, for homologous recombination-mediated replacement of the CYBB mutation without nuclease enhancement. In the current study, TALEN-mediated targeted insertion of a minigene consisting of the normal or codon-optimized cDNA of all 13 exons of CYBB without introns into the start site of exon 1 of the endogenous CYBB gene resulted in no detectable gp91 phox expression, indicating that intronic or other downstream non-coding elements are necessary for expression from the CYBB promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The WT hiPSCs lines T12 (WT#3) and S24 (WT#2) were provided by the Pediatric Endocrinology and Diabetology laboratory (Department of Pediatrics, University Clinic Carl Gustav Carus, TU Dresden, Germany). These hiPSCs lines were obtained from fibroblasts from healthy donors (Kind et al, 2010), reprogrammed by lentiviral transduction vector and validated as described in Laugsch et al (2016). The WT hiPSCs lines NP0040-8 (WT#1) provided by Center for Physiology and Pathophysiology, Institute for Neurophysiology, Medical Faculty, University of Cologne, Cologne, Germany was reprogrammed by episomal reprogramming vectors and validated according to EBiSC standards (NP0040-8 is available at EBiSC under accession name UKKi011-A; https://cells.ebisc.org/ UKKi011-A/).…”
Section: Wt Hipscsmentioning
confidence: 99%
“…Here, we perform a second step toward the translation ability of this strategy, by performing a proof of principle study on a mouse model of X‐linked CGD, a human immunodeficiency which has been the target of many attempts to gene therapy . Viral vector‐based trials for gene correction in humans have been reported, but the occurrence of undesired events and the concomitant introduction of programmable nucleases prompted the investigation of “gene editing” approaches to more precisely correct the nucleotide defect in iPSCs or directly in hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%